2010
DOI: 10.1111/j.1524-4725.2010.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Efficacy of Copper Bromide Plus/Yellow Laser (578 nm with 511 nm) for Treatment of Melasma in Asian Patients

Abstract: The potential application of an antiangiogenetic laser for the treatment of melasma specially accompanied by pronounced telangiectasia in Asian skin is a possible treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 25 publications
1
52
1
1
Order By: Relevance
“…In a recent pilot study, 10 Korean women with mixed or epidermal melasma were treated with a copper bromide laser emitting both wavelengths simultaneously at 2-week intervals for a total of 8 weeks. 84 MASI scores decreased modestly from an average of 12.3 pretreatment to 9.5 at the 1-month posttreatment follow-up. Using a chromameter, the authors noted measurable lightening of lesional skin after treatment, but the effects appeared to wane slightly at the 1-month posttreatment follow-up.…”
Section: Copper Bromide Lasermentioning
confidence: 85%
“…In a recent pilot study, 10 Korean women with mixed or epidermal melasma were treated with a copper bromide laser emitting both wavelengths simultaneously at 2-week intervals for a total of 8 weeks. 84 MASI scores decreased modestly from an average of 12.3 pretreatment to 9.5 at the 1-month posttreatment follow-up. Using a chromameter, the authors noted measurable lightening of lesional skin after treatment, but the effects appeared to wane slightly at the 1-month posttreatment follow-up.…”
Section: Copper Bromide Lasermentioning
confidence: 85%
“…The individual pulse cannot supply sufficient thermal energy to coagulate the vessels being treated. The summation of thermal energy from numerous pulses will coagulate the vessels16. Favorable results for the reduction of vascular erythema by 578 nm copper bromide laser have already been reported when treating vascular lesions like telangiectasia, port wine stains, spider nevi, and hemangioma10,17,18,19,20,21,22.…”
Section: Discussionmentioning
confidence: 99%
“…The copper bromide laser was consistently reported to have disappointing results in the literature with the exception of a Korean study published in 2010. [80][81][82] In the late 1990s, a study reported that the picosecond laser had superior efficacy than the nanosecond laser in tattoo removal. 83 The picosecond alexandrite laser was developed and shown to be effective in tattoo removal, 84,85 leading to its recent commercialization.…”
Section: New Laser Therapiesmentioning
confidence: 99%
“…[76][77][78][79][80] Although the conventional laser treatment of melasma using QS alexandrite laser and QS ruby laser has brought poor results, lowering the fluence or using the fractional mode is expected to widen the application of these lasers in melasma. The copper bromide laser was consistently reported to have disappointing results in the literature with the exception of a Korean study published in 2010.…”
Section: New Laser Therapiesmentioning
confidence: 99%